Risk factors of stunting among children living in an urban slum of Bangladesh: findings of a prospective cohort study - M. Munirul Islam; Kazi Istiaque Sanin; Mustafa Mahfuz; A. M. Shamsir Ahmed; Dinesh Mondal; Rashidul Haque; Tahmeed Ahmed (BMC, 2018)
Abstract Background Bangladesh is one of the 20 countries with highest burden of stunting globally. A large portion (around 2.2 million) of the population dwells in the slum areas under severe vulnerable conditions. Children residing in the slums are disproportionately affected with higher burden of undernutrition particularly stunting. In this paper, findings of a prospective cohort study which is part of a larger multi-country study are presented. Methods Two hundred and sixty five children were enrolled and followed since their birth till 24 months of age. Anthropometric measurements, dietary intake and morbidity information were collected monthly. Data from 9 to 12, 15-18 and 21-24 months were collated to analyze and report findings for 12, 18 and 24 months of age. Generalized estimating equation models were constructed to determine risk factors of stunting between 12 and 24 months of age. Result Approximately, 18% of children were already stunted (LAZ < -2SD) at birth and the proportion increased to 48% at 24 months of age. Exclusive breastfeeding prevalence was only 9.4% following the WHO definition at 6 months. Dietary energy intake as well as intakes of carbohydrate, fat and protein were suboptimal for majority of the children. However, in regression analysis, LAZ at birth (AOR = 0.40, 95% CI: 0.26, 0.61), household with poor asset index (AOR = 2.81, 95% CI: 1.43, 5.52; ref.: average asset index), being male children (AOR = 1.75, 95% CI: 1.04, 2.95; ref.: female) and age (AOR = 2.34, 95% CI: 1.56, 3.52 at 24 months, AOR = 2.13, 95% CI: 1.55, 2.92 at 18 months; ref.: 12 months of age) were the significant predictors of stunting among this population. Conclusion As the mechanism of stunting begins even before a child is born, strategies must be focused on life course approach and preventive measurement should be initiated during pregnancy. Alongside, government and policymakers have to develop sustainable strategies to improve various social and environmental factors those are closely interrelated with chronic undernutrition particularly concentrating on urban slum areas.